The role of talent management and employee engagement on employee retention mediated by job satisfaction - Alrianti, Alvina; Ekhsan, Muhamad (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
Retaining talented employees must be done to compete in the industrial world. The implementation of talent management is the company's effort in retaining its employees. In addition, fostering a sense of employee attachment to the company is also a strategy in retaining employees. The aim is to determine the effect of talent management and employee engagement on employee retention mediated by job satisfaction. The population is employees who work in electronics companies in the EJIP Cikarang industrial area. 90 respondents were used as samples with the sampling technique, namely the simple random sampling method. Data collection is done through google form and measured by Likert scale. The results are talent management contributes to employee retention, employee engagement does not contribute to employee retention, talent management contributes to job satisfaction, employee engagement contributes to job satisfaction. Job satisfaction contributes to employee retention, job satisfaction is able to mediate the relationship between talent management and employee engagement on employee retention. Mempertahankan karyawan yang bertalenta harus dilakukan untuk bersaing di dunia industri. Penerapan manajemen talenta merupakan upaya perusahaan dalam mempertahankan karyawannya. Selain itu, menumbuhkan rasa keterikatan karyawan terhadap perusahaan juga merupakan strategi dalam mempertahankan karyawan. Tujuannya yaitu untuk mengetahui pengaruh talent management dan employee engagement terhadap employee retention yang dimediasi oleh kepuasan kerja. Populasi nya adalah karyawan yang bekerja di perusahaan elektronik di kawasan industri EJIP Cikarang. 90 responden digunakan sebagai sampel dengan teknik pengambilan sampel yaitu metode simple random sampling. Pengumpulan data dilakukan melalui google form dan diukur dengan skala likert. Dianalisis menggunakan Smart PLS 3. Hasilnya yaitu talent management berkontribusi terhadap employee retention, employee engagement tidak berkontribusi terhadap employee retention, talent management berkontribusi terhadap kepuasan kerja, employee engagement berkontribusi terhadap kepuasan kerja. Kepuasan kerja berkontribusi terhadap employee retention, kepuasan kerja mampu memediasi hubungan antara talent management dan employee engagement terhadap employee retention.